Strategi Peningkatan Daya Saing Madrasah; Studi Kasus Madrasah Ibtidaiyah Negeri Madiun - Imam Tholkhah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2016)
This research is aimed at acknowledging competitiveness increase model and strategies in the Madura Public Islamic Elementary School. For years, this Islamic school has been in a really degraded condition. However, within the past few decades, it has been drastically reviving and able to prove itself as a superior and competitive Islamic school. This change then becomes attractive to be researched on so that the success achieved by this Islamic school can later be duplicated by other Islamic schools. This research is a qualitative research with case study approach. Data collection was performed through observations, interviews, group discussions and document tracing. This research results in finding that the factors of school principal leadership, learning innovations, teachers and quality school facilities are the main aspects that are able to increase this Islamic school’s quality and competitiveness. These factors have brought this Islamic school able to reach achievements in various fields and thereafter have brought a stream of people registering their children with this Islamic school.